MOLECULAR DOCKING STUDIES OF NEW ANTIHYPERTENSIVE DRUG BASED ON DELPHINIDIN-3-SAMBUBIOSIDE ANALOGUES USING ANTIOGENSIN I–CONVERTING ENZYME AS THE TARGET - HEENA PEETHAMBARAN; DEENA ANTONY C; NISHA GEORGE; ABHISHEK HARISH (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Hypertension is a major health concern which is responsible for various cardiovascular and renal disorders. Although being one of the most commonly prescribed medicines, antihypertensive drugs have been shown to have negative side effects for some patient groups, posing a need for the development of novel therapies. This study aimed to evaluate the potential of Delphinidin-3-sambubioside (D3S), an hibiscus anthocyanin, and its stereochemically altered analogs as angiotensin I–converting enzyme (ACE) inhibitors. Methods: The ACE inhibitory activity of D3S and its stereochemically altered analogs was evaluated using an in silico molecular docking methods. To determine the important interaction stabilizing the ligand-protein complexes, binding affinities were computed and molecular interaction studies were performed. The binding pocket’s druggability was also investigated. Results: The highest binding affinity was recorded for one of the analogs with a binding energy of −10.4 kcal/mol, which is greater than that obtained for D3S at −8.2 kcal/mol. Molecular interaction analysis of this analog demonstrated key hydrogen bond interactions with ACE residues along with other hydrophobic interactions and salt bridges at the active site stabilizing the protein-ligand complex. The possible druggable pocket was also predicted to explore any overlapping with binding regions and a drug score of 0.81 was obtained. Conclusion: The increased binding affinity and favorable interaction profile of the D3S analog, combined with reported pharmacokinetic properties, predict D3S analogs as a potential alternative to be further investigated in vitro and in vivo as antihypertensive agents.